2017
DOI: 10.1111/cbdd.13130
|View full text |Cite
|
Sign up to set email alerts
|

Identification of chlamydial T3SS inhibitors through virtual screening against T3SS ATPase

Abstract: Chlamydia trachomatis is a widespread sexually transmitted pathogen that resides within a special vacuole inside host cells. Although acute infection can be treated with antibiotics, chlamydia can enter persistent state, leading to chronic infection that is difficult to cure. Thus, novel anti-chlamydial compounds active against persistent chlamydia are required. Chlamydiae rely upon type III secretion system (T3SS) to inject effector proteins into host cell cytoplasm, and T3SS inhibitors are viewed as promisin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 36 publications
0
23
0
Order By: Relevance
“…Such information could facilitate the construction of a general model for designing small inhibitors targeting T3SS ATPases in various Gram-negative bacteria. In recent years, many small inhibitors targeting T3SS ATPases have been identified and developed against pathogens (Swietnicki et al, 2011 ; Gong et al, 2015 ; Grishin et al, 2018 ). Small-molecule compounds that bind to T3SS ATPases based on the nucleotide-bound Spa47 structure determined in the present work could obstruct the ATP-binding site and effectively inhibit catalytic activity.…”
Section: Discussionmentioning
confidence: 99%
“…Such information could facilitate the construction of a general model for designing small inhibitors targeting T3SS ATPases in various Gram-negative bacteria. In recent years, many small inhibitors targeting T3SS ATPases have been identified and developed against pathogens (Swietnicki et al, 2011 ; Gong et al, 2015 ; Grishin et al, 2018 ). Small-molecule compounds that bind to T3SS ATPases based on the nucleotide-bound Spa47 structure determined in the present work could obstruct the ATP-binding site and effectively inhibit catalytic activity.…”
Section: Discussionmentioning
confidence: 99%
“…Using the structure of EscN (SctN for EPEC; PDB ID: 2OBL), FliI (flagellar SctN; PDB ID: 2DPY) and a bovine F-type ATPase (PDB ID: 2JDI) as ATPase templates, Grishin et al (2018) screened a library of compounds that could potentially inhibit the Chlamydia trachomatis ATPase homologue, CdsN, which has no known structure but approximately 50% sequence identity with the SctN's of known structure. 103 The ATPase is the only conserved enzymatic activity of the T3SS apparatus itself, and is thus an attractive drug target. 104 Grishin and colleagues identified 16 top-scoring candidates in their virtual screening process, with 2 compounds exhibiting significant suppression of the C. trachomatis development cycle in mammalian cells at low μM concentrations without displaying significant toxicity in mammalian cells.…”
Section: Inhibitor Classes and Their Associated Mechanism Of Inhibitionmentioning
confidence: 99%
“…The authors probed potential structure-activity relationships, but no improvements were found. 103 Case et al (2018) identified 3 non-competitive inhibitors of Spa47 (SctN of Shigella flexneri) through virtual screening techniques and were predicted to bind at the interface between protomers based on modelling the oligomeric structure of Spa47 after a heterohexameric F-type ATPase. 105 Two inhibitors functioned in vivo, exhibiting almost no secretion without compromising S. flexneri or HeLa viability.…”
Section: Inhibitor Classes and Their Associated Mechanism Of Inhibitionmentioning
confidence: 99%
See 2 more Smart Citations